Standardization of Predictive cluttering disorder inventory on Arab environment - Esmaeil, Mahmoud Atteia Mahmoud (Dirasat: Human and Social Sciences, 2024)
Objectives:The study aimed to standardize the Predictive cluttering inventory and verify its psychometric properties, including validity, reliability criteria, and correction mechanism, so that it can be used as a scientefic tool applicable to the Arab environment by specialists in diagnosis, follow-up, and intervention programs. Methods:the study depends on the descriptive method where the researcher translated the Predictive cluttering inventory accurately, and applied it to the Standardization sample (130) specialist in the treatment of speech and language disorders In the Arab world, they were selected randomly. Their ages range between 25-55 years, and they have experience in dealing with cases of cluttering, and after applying the Predictive cluttering inventory, appropriate statistical tests were applied. Results: The results showed that the Predictive cluttering inventory has appropriate levels of Face/structural/ discriminatory /correlation validity. the results showed high coefficients of alpha Cronbach stability/half fragmentation/ reapplication, which indicates the validity and reliability of the Predictive cluttering inventory for application by specialists to measure, diagnose and follow up speech fluency disorder in the Arab environment, The results of the study were discussed in light of the study's literature. Concolusion:The study recommends that specialists apply the the Predictive cluttering inventory as a standardized Arab diagnostic tool, and conduct further studies to verify the psychometric properties of the Predictive cluttering inventory and use it in diagnosis, follow-up, and intervention programs in the Arab environment.